Anatomy for the Generic Surgical Sciences Examination (GSSE) - Mirjalili, S. Ali (Springer Singapore : Imprint: Springer, 2017)
This book is designed for Generic Surgical Sciences Examination (GSSE). This collection of questions and answers as well as short notes is intended to assist junior doctors in successfully sitting the GSSE. The questions are specifically designed to highlight key surgical anatomy, and are supplemented by images that replicate "spot-test" type questions. Illustrations are used here to highlight particular anatomical relationships that are difficult to grasp. Beyond the GSSE, this resource will be invaluable for those undertaking study for specialty-specific anatomy examinations, or the anatomy component of the fellowship examination. This is a "prep course" specifically designed for passing the Generic Surgical Science Examination required by the Royal Australasian College of Surgeons (RACS).